Controlling the Origins of Inflammation with a Photo-Active Lipopeptide Immunopotentiator - Mancini, Rock J. (Angew Chem Int Ed Engl, 2015)
Inflammatory immune responses are mediated by signaling molecules that are both produced and recognized across highly heterogeneous cell populations. As such, studying inflammation using traditional immunostimulants is complicated by paracrine and autocrine signaling that obscures the origin of a propagating response. To address this challenge, we developed a small molecule probe that can photosensitize immune cells allowing for light-mediated inflammation. We use this probe to control the origin of inflammation using light. Following this motif, inflammation was induced originating from fibroblasts or dendritic cells. We report the contributions of fibroblasts and dendritic cells in initiating inflammation in heterogeneous co-culture which provides insights for the future development of vaccines and treatment of inflammation.